Low limb prostheses and complex human prosthetic interaction: A systematic literature review - Domínguez-Ruiz, Adan; López-Caudana, Edgar Omar; Lugo-González, Esther; Espinosa-García, Francisco Javier; Ambrocio-Delgado, Rocío; García, Ulises D.; López-Gutiérrez, Ricardo; Alfaro-Ponce, Mariel; Ponce, Pedro (Frontiers in Robotics and AI, 2023)
A few years ago, lower limb prosthetics triggered new technological development in diverse areas such as mobility, comfort, and design, which have been essential to improving the quality of life of individuals with lower limb disablitlity. To design lower limb prosthetics, critical elements like the amputation level, user morphology, human-prosthetic interaction, and user lifestyle must be considered. Hence, several technologies have been employed to accomplish the end user's needs, for example, advanced materials, automatic control, electronics, energy management, signal processing, and artificial intelligence. This paper presents a systematic literature review on such technologies, to identify the latest advances, challenges, and opportunities in developing lower limb prostheses with the analysis on the most significant papers. Prostheses for walking in different terrains were illustrated and examined, with the kind of movement the device should perform by considering the electronics, automatic control, and energy efficiency. Results show a lack of a specific and generalised structure to be followed by new developments, gaps in energy management and improved smoother patient interaction. Additionally, Human Prosthetic Interaction (HPI) is a term introduced in this paper since no other one had integrated this interaction in communication between the artificial limb and the end-user. The main goal of this paper is to provide, with the found evidence, a set of steps and components to be followed by new researchers and experts looking to improve knowledge in this field.